2020
DOI: 10.1038/s41550-020-1150-z
|View full text |Cite
|
Sign up to set email alerts
|

A protostellar system fed by a streamer of 10,500 au length

Abstract: Binary formation is an important aspect of star formation. One possible route for close-in binary formation is disk fragmentation [1,2,3] . Recent observations show small scale asymmetries (<300 au) around young protostars [2,4] , although not always resolving the circumbinary disk, are linked to disk phenomena [5,6] . In later stages, resolved circumbinary disk observations [7] (<200 au) show similar asymmetries, suggesting the origin of the asymmetries arises from binary-disk interactions [8,9,10] . We obser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
130
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(147 citation statements)
references
References 56 publications
17
130
0
Order By: Relevance
“…We report the presence of accretion streamers (already observed in the low-mass regime, see Pineda et al 2020), which are reminiscent of the accretion channels found by Seifried et al (2015) and the bridges in the study of Kuffmeier et al (2019) and Kuffmeier et al (2020). In agreement with Seifried et al (2015), ram pressure dominates magnetic pressure, but we further show that magnetic pressure is also dominated by thermal pressure.…”
Section: Comparison With Previous Worksupporting
confidence: 77%
“…We report the presence of accretion streamers (already observed in the low-mass regime, see Pineda et al 2020), which are reminiscent of the accretion channels found by Seifried et al (2015) and the bridges in the study of Kuffmeier et al (2019) and Kuffmeier et al (2020). In agreement with Seifried et al (2015), ram pressure dominates magnetic pressure, but we further show that magnetic pressure is also dominated by thermal pressure.…”
Section: Comparison With Previous Worksupporting
confidence: 77%
“…These include emission from an envelope/accretion streamer or outflow cavity, or perturbations by an unseen companion. This arc is similar to the streamer that is feeding material from the local environment onto Per-emb-2 (Pineda et al 2020), [BHB2007] 1 (Alves et al 2020), SU Aur (Ginski et al 2021), and, on a smaller scale, HL Tau (Yen et al 2019). However, what is unique about the emission around [MGM2012] 512 is that it is detected in the continuum.…”
Section: Structure Around [Mgm2012] 512mentioning
confidence: 86%
“…Nevertheless, the observed SO emission is consistent with the geometry seen in the H 2 CO emission. The morphology near the protostar in the H 2 CO and C 18 O emission and the apparent symmetry in the SO emission strongly suggest that these features are part of an outflow structure, rather than a structure formed from gas accreting toward the protostar as seen in the source Per-emb-2 by Pineda et al (2020).…”
Section: Linear Structure In the Northwest To Southeast Directionmentioning
confidence: 95%